(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
Cattle breeding is the leading branch of animal husbandry in Uzbekistan, playing an important role in providing the population with high-quality food products such as milk and meat. The daily needs of livestock for the production of these products, that is, the main part of the feed base, is 65-70% of corn silage and grain. This naturally increases the demand for scientific and practical work on the development of a high-yielding and climate-resistant corn plant in our country and in the world.